Responsibility of Financial Management Institution Amil Zakat for Transparency - Kudhori, Ahmad; Pandowo, Hedi (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2020)
Knowing the understanding and preparation of financial reports by financial managers as a form of transparency is the aim of this study. Multiple case studies at the national amil zakat institution which is part of the regional zakat organization forum (FOZDA) in Madiun with descriptive qualitative analysis as the research method used. To collect data, the methods of observation, documentation and in-depth interviews were used to address informants who are in each of the zakat institutions that are members of the FOZDA. The results of this study indicate that the understanding of accounting, financial reports and applicable standards of the financial managers of the amil zakat institution is different, which is caused by the educational background, years of service and position of the institution in Madiun, whether as a branch office, unit or outlet. However, office governance, finance, management and human resources in institutions can work together, so that the compliance of the amil zakat institution in carrying out accounting (accounting) which produces output in the form of financial reports can run well, as a form of transparency and accountability to donors.